Assessing the impact of social grants on inequality: A South African case study - Reinhard Schiel; Murray Leibbrandt; David Lam (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The democratic government in South Africa has developed a system of social grants to combat the high levels of poverty and inequality inherited from the apartheid regime. With the help of modest economic growth and an associated increase in per capita household income, the introduction and expansion of social grants has helped alleviate the inherited burden of poverty. On the other hand income inequality has remained stubbornly high in post-apartheid South Africa and the role of these grants in inequality reduction remains unclear. We use national household survey data from 1993 and 2008 and the major income inequality decomposition techniques in order to assess the impact of a change in these government transfers on inequality. This South African case study allows for a side-by-side assessment of these income inequality decomposition techniques. We find that the social assistance awarded to the elderly has contributed dramatically to the decline in poverty but has not reduced income inequality. On the other hand social protection programs directed at child minders of poor children had an equalizing effect. More recent decomposition techniques allow us to net out the effect of changes in household composition on inequality from these impacts. This is shown to notably lower the direct impact of the social grants on inequality.
Keywords: H53; H55; I3; 330; social grants; household survey data; income inequality; South Africa